2005
DOI: 10.1115/1.1944027
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Simulation of Sandstone Acidizing

Abstract: We have developed a fine-scale model of the sandstone core acid flooding process by solving acid and mineral balance equations for a fully three-dimensional flow field that changed as acidizing proceeded. The initial porosity and mineralogy field could be generated in a correlated manner in three dimensions; thus, a laminated sandstone could be simulated. The model has been used to simulate sandstone acidizing coreflood conditions, with a 1in.diam by 2in. long core represented by 8000 grid blocks, each having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This highly nonuniform structure created by acid in carbonates results in much deeper penetration of acid into the formation than is thought possible in sandstones. Because the wormholes increase effective permeability greatly while only a small portion of the matrix is actually dissolved, the creation of wormholes is an efficient and desirable mode of matrix acidizing (Li et al 2005). Carbonate acidization undergoes mode changes with increase of acid flow rate.…”
Section: Conclusion and Suggestions For Future Workmentioning
confidence: 99%
“…This highly nonuniform structure created by acid in carbonates results in much deeper penetration of acid into the formation than is thought possible in sandstones. Because the wormholes increase effective permeability greatly while only a small portion of the matrix is actually dissolved, the creation of wormholes is an efficient and desirable mode of matrix acidizing (Li et al 2005). Carbonate acidization undergoes mode changes with increase of acid flow rate.…”
Section: Conclusion and Suggestions For Future Workmentioning
confidence: 99%
“…Hence, in this research, a general numerical model that is specifically focusing on HBF 4 sandstone acidizing is presented. This model is developed based on the mud acid acidizing modelling approach by Li et al (2004). The HBF 4 model has been developed based on the Finite Element Method (FEM).…”
Section: Hbf 4 Numerical Model Developmentmentioning
confidence: 99%
“…The detail chemical reaction processes are shown in Eqs. (1)- (4) (Li et al 2004 In the form of aqueous solution, HBF 4 will hydrolyze step-bystep to produce HF progressively. The first step of the hydrolysis process is known as the slowest reaction, hence determining the rate of hydrolysis.…”
Section: Chemical Reaction Modelmentioning
confidence: 99%
“…They found that dissolution and precipitation do not occur simultaneously. Li et al [11] built a linear acid flooding model to simulate linear core flooding at an experimental scale with the consideration of the heterogeneities of minerals and flow fields. Li et al [12] built a radial acidizing model and considered the effect of the temperature field on the reaction, but they did not consider the effect of the heterogeneities.…”
Section: Introductionmentioning
confidence: 99%